Novel District Heating Systems: Methods and Simulation Results - David Huber; Viktoria Illyés; Veronika Turewicz; Gregor Götzl; Andreas Hammer; Karl Ponweiser (Energies, 2021)
Fifth-generation district heating and cooling (5th DHC) systems offer promising approaches to decarbonizing space heating, cooling and domestic hot water supply. By using these systems, clustered buildings combined with industrial waste heat can achieve a net-zero energy balance on a variety of time scales. Thanks to the low exergy approach, these systems are highly efficient. As part of the Smart Anergy Quarter Baden (SANBA) project, the thermal energy grid simulation tool TEGSim has been further developed and used to design an ultra-low-temperature district heating (ULTDH) network with hydraulic and thermal components fitted to the specific regional characteristics of the investigated case. Borehole thermal energy storage (BTES) used as seasonal storage ensures long-term feasibility. The annual discrepancy of input of thermal energy provided by space cooling and output of energy demanded by space heating and domestic hot water is supplied by an external low-grade industrial waste heat source. This paper presents the functionality of the simulation and shows how to interpret the findings concerning the design of all components and their interplay, energy consumption and efficiencies.